PERAN MUSYAWARAH GURU MATA PELAJARAN DALAM MENINGKATKAN PENGEMBANGAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM SMA DI KABUPATEN JOMBANG - Muhamad Khoirur Roziqin; Sholeh Abdul Baqi (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2021)
This study aims 1.) to find out Islamic Religious Education Subjects at the Jombang Regency State High School, 2.) to find out how the role of Subject Teacher Guidance in improving the professionalism of Islamic Religious Education Teachers in high school in Jombang Regency. This research is a qualitative research, which uses research procedures that produce descriptive data in the form of written or spoken words from organizations and behaviors that are observed and directed at natural settings and individuals holistically (as a whole). The research data were then analyzed using descriptive analysis, namely the analysis of data displayed in the form of descriptive reports and descriptions, using inductive thinking. Inductive thinking is a way of drawing conclusions from empirical facts and then drawing generalizations. The results obtained from the Subject Teacher Meetings include: 1. The growing willingness of PAI teachers to always improve their performance as teachers by following existing positive changes, 2. PAI teachers are motivated to become better because they relate a lot to other people so that insight becomes increased. 3. Islamic religious education teachers know the latest news or issues in the world of education because the Subject Teacher Consultation is a mediator from the national education office and the department of religion in delivering the implementation of education policies, curriculum changes, and others. 4. With training and upgrading, the creativity and skills of Islamic Religious Education teachers will develop and be honed.